Central Mechanisms Underlying Tactile Suppression - Führer, Elena; Justus Liebig University Giessen (My University, 2026)
Tactile sensations on a moving limb and the neural responses associated with them are suppressed. This phenomenon has often been described as a general reduction in somatosensory processing during movement. However, converging evidence instead supports a more selective form of sensory gain control shaped by central predictive mechanisms and motor context. Using psychophysics, electroencephalography (EEG), and kinematic analyses, this thesis examines how precise sensorimotor predictions shape tactile suppression and how tactile sensitivity and cortical processing vary with feedback demands during goal-directed reaching. First, I demonstrate that suppression of external vibrotactile probes during motor planning is tuned to specific sensorimotor predictions. Next, I characterize somatosensory evoked potentials (SEPs) to naturalistic high-frequency vibrotactile stimulation, addressing a gap in the EEG literature that has predominantly relied on electrical nerve stimulation. I quantify how SEP amplitudes scale with vibration intensity and compare vibrotactile with electrical stimulation, revealing distinct early processing for both modalities. Using this naturalistic stimulation paradigm, I then show that tactile suppression and early cortical gating follow the same temporal pattern across a goal-directed reaching movement. This pattern indicates that tactile processing during complex movements reflects state-dependent feedback demands. Together, these findings characterize tactile suppression and gating as flexible, precise forms of predictive sensory gain control at early stages of sensorimotor integration, likely mediated by cortical and corticospinal circuits. In this view, tactile suppression reflects the behavioral expression of sensory gain regulation, through which central control shapes the influence of somatosensory signals on movement.
Keywords: Sensory attenuation; Somatosensory evoked potentials; Tactile suppression; Sensorimotor predictions; ddc:150